A few-layered graphene on alumina nanofibers for electrochemical energy conversion. (July 2015) - Hussainova, Irina; Ivanov, Roman; Stamatin, Serban N.; Anoshkin, Ilya V.; Skou, Eivind M.; Nasibulin, Albert G.
Abstract: A few-layered graphene on the surface of highly aligned alumina nanofibers (ANFs) with an aspect ratio of 10 7 was synthesized in a single-step catalyst-free direct chemical vapor deposition process. The product, graphenated alumina nanofibers (G-ANFs), consisting of the ceramic nanofibers surrounded by the conductive and inert few-layered graphene, is a promising material for electrochemical applications. The synthesized material has been demonstrated to be an excellent electrocatalyst support for Pt particles in fuel cells. A 1.5-fold improvement in the mass activity has been obtained for Pt/G-ANF in comparison to the commercially available Pt/C. The electrochemical stability was found to be outstanding for acidic medium electrochemistry. Their remarkable stability and unique structure opens a new avenue for the use of this material in various electrochemical energy conversion technologies.